Healthy percentage body fat ranges: an approach for developing guidelines based on body mass index. - Gallagher, D; Heymsfield, S; Heo, M; Jebb, SA; Murgatroyd, P; Sakamoto, Y (2000)
BACKGROUND: Although international interest in classifying subject health status according to adiposity is increasing, no accepted published ranges of percentage body fat currently exist. Empirically identified limits, population percentiles, and z scores have all been suggested as means of setting percentage body fat guidelines, although each has major limitations. OBJECTIVE: The aim of this study was to examine a potential new approach for developing percentage body fat ranges. The approach taken was to link healthy body mass index (BMI; in kg/m(2)) guidelines established by the National Institutes of Health and the World Health Organization with predicted percentage body fat. DESIGN: Body fat was measured in subjects from 3 ethnic groups (white, African American, and Asian) who were screened and evaluated at 3 universities [Cambridge (United Kingdom), Columbia (United States), and Jikei (Japan)] with use of reference body-composition methods [4-compartment model (4C) at 2 laboratories and dual-energy X-ray absorptiometry (DXA) at all 3 laboratories]. Percentage body fat prediction equations were developed based on BMI and other independent variables. RESULTS: A convenient sample of 1626 adults with BMIs < or =35 was evaluated. Independent percentage body fat predictor variables in multiple regression models included 1/BMI, sex, age, and ethnic group (R: values from 0.74 to 0.92 and SEEs from 2.8 to 5.4% fat). The prediction formulas were then used to prepare provisional healthy percentage body fat ranges based on published BMI limits for underweight (<18.5), overweight (> or =25), and obesity (> or =30). CONCLUSION: This proposed approach and initial findings provide the groundwork and stimulus for establishing international healthy body fat ranges.